2020
DOI: 10.1177/1091581820905092
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Characterization in Cynomolgus Monkeys, Beagle Dogs, and Göttingen Minipigs

Abstract: Intrathecal administration is an important route for drug delivery, and in pharmacology and toxicology studies, cerebrospinal fluid (CSF) collection and analysis is required for evaluating blood–brain barrier penetration and central nervous system exposure. The characteristics of CSF in commonly used nonrodent models are lacking. The purpose of this study is to evaluate and provide some insights into normal cellular and biochemical composition of CSF as well as diffusion potential following intrathecal injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition to considering CSF volume and turnover rates when evaluating large animal models, it is also important to compare diffusion rates and composition of CSF between species. In one study, a differential cell count found a comparable ratio of lymphocyte to monocytoid cells in both cynomolgus monkeys and beagle dogs ( Ballesteros et al, 2020 ), but a significantly lower ratio in Gottingen minipigs. This same study also assessed diffusion rates after an intrathecal injection of a contrast agent and showed that beagle dogs had the longest diffusion times with the infusate covering the most distance, followed by NHPs, and lastly minipigs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to considering CSF volume and turnover rates when evaluating large animal models, it is also important to compare diffusion rates and composition of CSF between species. In one study, a differential cell count found a comparable ratio of lymphocyte to monocytoid cells in both cynomolgus monkeys and beagle dogs ( Ballesteros et al, 2020 ), but a significantly lower ratio in Gottingen minipigs. This same study also assessed diffusion rates after an intrathecal injection of a contrast agent and showed that beagle dogs had the longest diffusion times with the infusate covering the most distance, followed by NHPs, and lastly minipigs.…”
Section: Discussionmentioning
confidence: 99%
“…The CSF sample collection and assay followed standard protocols and have been described previously. 49 In short, after monkeys fasted for at least 8 h, a lumbar puncture was performed at the intervertebral space L3-L4 or L4-L5 using a standard needle. CSF was collected into a 1.5 ml sterile microtube (Axygen, MCT-150-C) and immediately frozen at −80 °C.…”
Section: Csf and Plasma Sample Collection And Biomarker Measurementsmentioning
confidence: 99%